Acoustic courtship songs in males of the fruit fly Anastrepha ludens (Diptera: Tephritidae) associated with geography, mass rearing and courtship success - Hanson Snortun, Paul (2009)
artículo (arbitrado)--Universidad de Costa Rica. Escuela de Biología, 2009